Geotechnical Properties of Rubber Tires and Sediments Mixtures - Sellaf, H.; Trouzine, H.; Hamhami, M.; Asroun, A. (Engineering, Technology & Applied Science Research, 2014)
An experimental work was undertaken to study the effect of rubber tires on the geotechnical properties of a dredged sediment, using a mixing ratio of large size. For comparison, two types of soil were studied (dredged sediment from Fergoug dam and Tizi Tuff from the north west of Algeria). Taking into account the high compressibility and the low water absorption of the rubber tires, grain size analysis, density, Atterberg limits analysis, chemical composition, direct shear tests, loading-unloading tests, modified Proctor and CBR tests are performed on the two soils and their mixtures with different scrap tire rubber (10, 20, 25 and 50%). The results show that liquid limits and plastic indexes decrease with the scrap tire rubber content and that the decrease is more significant for soil with high plasticity. Cohesion also decreases with scrap tire rubber content when the internal friction angle is vacillating. Compression and recompression indexes increase gradually with the scrap tire rubber content and the variation for compression index is more significant for the two soils. Compaction characteristics and CBR values decrease with scrap tire rubber content. The CBR values for W=3% are important compared to those with W=5% excepted for mixture with (75% tuff and 25% scrap tire rubber). The results show that the scrap tire rubber can be used as a reinforcement material for dredged soil, but with a content that should not highly affect the compressibility.